2019
DOI: 10.7570/jomes.2019.28.4.262
|View full text |Cite
|
Sign up to set email alerts
|

Association between Abdominal Obesity and Cardiovascular Risk Factors in Adults with Normal Body Mass Index: Based on the Sixth Korea National Health and Nutrition Examination Survey

Abstract: BackgroundAbdominal obesity predisposes individuals to cardiovascular disease, but the data in adults with normal body mass index (BMI) are relatively rare. This study aimed to evaluate the characteristics of subjects with normal BMI and abdominal obesity and to identify the relationship between central obesity and cardiovascular risk factors in normal BMI adults in Korea.MethodsTen thousands six hundred thirty-four adults with BMI between 18.5 to 24.9 kg/m2 who participated in the sixth Korea National Health … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 17 publications
1
20
0
1
Order By: Relevance
“…Furthermore, physical measurement indexes such as waist circumference were significantly decreased in this study. Previous studies asserted that abdominal obesity has been identified as an important risk factor for metabolic syndrome and CVD [49,50]. Also, the other studies have shown that waist circumference was reduced relatively more in women than men [49,51].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, physical measurement indexes such as waist circumference were significantly decreased in this study. Previous studies asserted that abdominal obesity has been identified as an important risk factor for metabolic syndrome and CVD [49,50]. Also, the other studies have shown that waist circumference was reduced relatively more in women than men [49,51].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies asserted that abdominal obesity has been identified as an important risk factor for metabolic syndrome and CVD [49,50]. Also, the other studies have shown that waist circumference was reduced relatively more in women than men [49,51]. Furthermore, Siu and colleges presented that one year of regular yoga training was effective on the improvement of waist circumference in middle-aged and older adults with metabolic syndromes [52].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, PED was an independent risk factor for CKD progression in this study; subjects with PED showed 3.26 times higher risk of CKD progression. CKD shares common risk factors and pathophysiological mechanisms with ASCVD [24][25][26]. The combined risk of ASCVD and CKD was increased 4.12 times by PED at the baseline.…”
Section: Discussionmentioning
confidence: 98%
“…It was reported that AO with normal BMI was associated with cardiovascular diseases, and was related to dyslipidemia in women. [20] Another South Korean study showed that general obesity without AO was not associated with a higher risk of cardiovascular diseases. [21] Another major nding of this study was that women with maternal AO history have a higher risk of developing AO.…”
Section: Discussionmentioning
confidence: 99%